2017
DOI: 10.14257/ijsia.2017.11.1.10
|View full text |Cite
|
Sign up to set email alerts
|

A Classification Scheme for Cybersecurity Models

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Paper [4] reports a generalized classification of software safety testing models. A criterion for assessing the effectiveness of testing has been proposed.…”
Section: The Aim and Objectives Of The Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Paper [4] reports a generalized classification of software safety testing models. A criterion for assessing the effectiveness of testing has been proposed.…”
Section: The Aim and Objectives Of The Studymentioning
confidence: 99%
“…Transitions (1-3) and (2-3) correspond to the process of preparing test documentation and test control bench. Transition (3)(4) formalizes the process of pre-evaluation of the tested object (architecture, completeness of information, etc. ), as well as planning of the study.…”
Section: 2 Developing a Gert-network Scheme Of The Process To Prepare For Security Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the literature has shown that at present there are various approaches to mathematical formalization and modeling of software security testing processes. These models are presented in works [1][2][3][4][5][6][7][8][9][13][14][15].…”
Section: Introductionmentioning
confidence: 99%